Enzymatic activity in soil treated with exogenous organic matter - Siebielec, Sylwia; Siebielec, Grzegorz; Ukalska-Jaruga, Aleksandra; Urbaniak, Magdalena (Polish Journal of Agronomy, 2021)
The content of organic matter affects the quality and productivity of agricultural soils. Due to the shortage of manure as the basic source of organic matter for agricultural soils, al- ternative and commonly available exogenous sources of organic matter, such as sewage sludge and bottom sediments, are taken into account. The aim of the study was to evaluate the effect of the addition of various types of manure, municipal sewage sludge and bottom sediments on the enzymatic activity of soils (dehydrogenases, acidic and alkaline phosphatases). Manure and sludge were applied to the soil in two doses, corresponding to 20 and 40 tons of dry matter of material per ha. The control was soil fertilized with ammonium nitrate in the amount corresponding to 170 kg N per ha. The experiment included 2 different variants of the same fertilization combinations: without plants and with a test plant (Sinapis alba L.). The greenhouse experiment showed the stimulating effect of one of the municipal sewage sludge and poultry manure. On the other hand, the introduction of bottom sediments to the soil limited its enzymatic activity.